"Once you get one maternal death, it's like the whole world is dropping on you": experiences of managing maternal mortality amongst obstetric care providers in Ghana - Anna Stabnick; Michael Yeboah; Johnny Arthur-Komeh; Frank Ankobea; Cheryl A. Moyer; Emma R. Lawrence (BMC, 2022)
Abstract Background Maternal mortality has a significant global impact, especially in low-resource settings. Little prior research has been conducted on the potential effects of poor maternal outcomes on the personal and professional well-being of healthcare providers. This study explores the in-depth experiences and perspectives of obstetric providers in Ghana who work in a setting with frequent maternal mortalities. Methods This is a qualitative study of semi-structured interviews conducted at the Komfo Anokye Teaching Hospital in Ghana. Participants were obstetric healthcare providers, defined as midwives, house officers currently rotating on the obstetrics/gynecology service, and obstetrician/gynecologists at any training or practice level (residents, fellows, and specialists). Interviews were audio-recorded, transcribed verbatim, and uploaded into NVivo for qualitative analysis. Using the Attride-Stirling qualitative model, an incremental and iterative process was used to code interviews with keyword phrases and develop a framework of organizing and global themes. Results Interviews were conducted with 27 participants-15 midwives and 12 physicians (three obstetrician/gynecologist residents, six obstetrician/gynecologist specialists, and three house officers), with sample size determined by data saturation. Obstetric providers' experiences in a setting with frequent maternal mortalities were dependent on their level of preparedness to manage maternal mortalities and the workplace environment. Providers' level of preparedness was dependent on both the training they had received on the medical management of obstetric emergencies, as well as a lack of training on the mental health aspects of coping with maternal mortality. The impact of the workplace environment was dependent on systems failures and limited resources, blame from colleagues and supervisors, and a lack of support in the workplace. In turn, obstetric providers' experiences managing frequent maternal mortalities impacted their clinical care performance and mental health. Conclusions Maternal deaths have profound personal and professional impacts on the healthcare providers who manage them. A large need exists for additional institutional training and support for obstetric providers who manage maternal mortality, especially in low-resource settings like Ghana.